Industrial training report: Baker Hughes Kuala Lumpur - Zakaria, Nur Izzah Hazirah (Universiti Teknologi MARA, Perlis, 2024)
The period I spent as an Indirect Tax Intern in the Global Tax Department at Baker Hughes Kuala Lumpur provided me with invaluable knowledge and exposure to international taxation. My main responsibilities including filing Value Added Tax and Withholding Tax for the Thailand firm on a monthly basis and ensuring that all deadlines were met precisely. In addition, I helped senior tax specialists extract and check invoices, which improved my attention to detail and analytical skills. My work also required me to contact with local authorities, such as visiting the Inland Revenue Board to collect Withholding Tax and delivering Voluntary Disclosure Program documentation to customs, which gave me actual experience with tax compliance processes. In this report, SWOT analysis for Baker Hughes revealed numerous significant aspects. A hybrid workplace and strong employee empowerment and development initiatives are among the company's strengths. However, weaknesses such as time zone differences and excessive workloads were also discovered. Opportunities include technology integration and prospective government collaborations, while threats include intense competition and volatile oil prices. In addition, a thorough financial analysis was also undertaken, with emphasis on profitability, leverage, efficiency, and liquidity ratios. The investigation indicated that Baker Hughes has low profitability measures, high leverage ratios, less efficient asset utilization and stable liquidity ratios. By completing this analysis, it gives actionable insights that can help Baker Hughes find areas of strategic improvement. Recommendations such as work life balance initiatives and cross functional collaboration ensuring the organization remains competitive in the ever-changing energy industry Lastly, working at Baker Hughes helped shape my professional development by providing me with new perspectives. Experience at Baker Hughes has been a memorable one and I am convinced that the skills and knowledge I have gained will benefit me in future endeavors.